2020
DOI: 10.1073/pnas.2007635117
|View full text |Cite
|
Sign up to set email alerts
|

In situ bone regeneration of large cranial defects using synthetic ceramic implants with a tailored composition and design

Abstract: The repair of large cranial defects with bone is a major clinical challenge that necessitates novel materials and engineering solutions. Three-dimensionally (3D) printed bioceramic (BioCer) implants consisting of additively manufactured titanium frames enveloped with CaP BioCer or titanium control implants with similar designs were implanted in the ovine skull and at s.c. sites and retrieved after 12 and 3 mo, respectively. Samples were collected for morphological, ultrastructural, and compositional analyses u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 61 publications
1
38
0
Order By: Relevance
“…The latter finding is also of clinical interest, emphasizing the important role of the initial inflammatory response after surgery and material implantation for triggering the subsequent regenerative processes. In addition, there is mounting evidence that calcium pyrophosphate can enhance bone formation in vivo when mixed with calcium phosphate cement [16,28]. We have demonstrated two mechanisms that may contribute to this phenomenon.…”
Section: Ppi Downregulate Sox9 Expression In Mscsmentioning
confidence: 75%
See 2 more Smart Citations
“…The latter finding is also of clinical interest, emphasizing the important role of the initial inflammatory response after surgery and material implantation for triggering the subsequent regenerative processes. In addition, there is mounting evidence that calcium pyrophosphate can enhance bone formation in vivo when mixed with calcium phosphate cement [16,28]. We have demonstrated two mechanisms that may contribute to this phenomenon.…”
Section: Ppi Downregulate Sox9 Expression In Mscsmentioning
confidence: 75%
“…The physiological impact of this finding is that PPi may prolong the survival of recruited monocytes, thereby altering both the duration and magnitude of inflammatory signaling. These observations indicate that the role of monocytes and macrophages during bone regeneration induced by pyrophosphate-containing bone ceramics [16,17,28] should be explored.…”
Section: Ppi Increases the Survival Of Primary Human Monocytes And Mscsmentioning
confidence: 94%
See 1 more Smart Citation
“…Uncertainty persists regarding the implications of the timing of CP in terms of complication rates and potential bene ts [2,3,35,39]. Materials for reconstruction of cranial defect ideally provide osteoinductive and osteoconductive properties to promote structural and functional restoration [25]. Autologous bone ap reinsertion is common after hemicraniectomy.…”
Section: Introductionmentioning
confidence: 99%
“…However, all calcium phosphate materials do not behave in the same manner, and therefore large efforts have been carried out to optimize properties such as phase composition, substitute ions, porosity, drug delivery and implant design [8][9][10]. Recently, a particular calcium phosphate formulation containing monetite, β-tricalcium phosphate (β-TCP) and β-calcium pyrophosphate (β-CCP) has demonstrated promising bone regenerating properties in vivo [11][12][13][14][15]. The formulation was developed for use in a solid mosaic-scaffold for patients with severe skull defects, in which it was shown that vascularized bone covered the material after 50 months [11,12].…”
Section: Introductionmentioning
confidence: 99%